Obtaining chitosan from fishing residues and its potentiometric titration - Torres, Blanca Sarahi Ovalle; Torres, Oscar Barraza; López, Jorge Andrés Hernández; Esteban, Peña Peña (Brazilian Journal of Science, 2023)
Chitin is the most abundant natural biopolymer followed by cellulose and is present in a large number of living organisms, such as fungi, insects and crustaceans, from which chitosan is obtained and its application to different areas of medicine has currently been demonstrated. pharmacology, cosmetics, agriculture, industry, etc. The quality of this compound is important due to the applications that it potentially presents, deacetylation or potentiometric titration, is one of the main parameters that determines said property, likewise, it allows the final obtaining of chitin, therefore, the objective of This work was to obtain chitin and chitosan from three different samples of crustacean exoskeletons from a fishing field with high productivity and environmental contamination. The results obtained indicate a degree of deacetylation greater than 70%, with a variable relative humidity between the samples (0.96, 0.089 and 0.47%) and ashes (18.86, 0.0484 and 29.19%), while a percentage of inorganic matter of the 12-16%. This means that the quality of the product that was obtained is considered acceptable and that the variations between the samples may be related to some factors such as food and origin of the raw material.